Unveiling the fate of adhering bacteria to antimicrobial surfaces: expression of resistance-associated genes and macrophage-mediated phagocytosis - Alves, Diana (2018)
Since most antibacterial coatings reported to fight biomaterial-associated infections (BAI) fail in completely preventing bacterial colonization, it is crucial to know the impact of that small fraction of adhered bacteria in BAI recrudescence. This study aims to understand the fate of Staphylococcus aureus able to adhere to an antimicrobial coating previously developed, in terms of potential development of bacterial resistance and their macrophage-mediated phagocytosis. Antimicrobial coating comprised the co-immobilization of Palm peptide and DNase I onto polydimethylsiloxane. Expression of genes associated to resistance and virulence mechanisms showed that cells in contact with antimicrobial surfaces for a long period of 30 days, exhibit genes equally or less expressed, as compared to cells recovered from control surfaces. Recovered cells also exhibit the same susceptibility patterns, which strengthens the evidence of no resistance development. Remarkably, cells adhered to modified surfaces shows a reduced metabolic activity upon vancomycin treatment unlike the cells found on control surfaces, which can be identified as a clinical opportunity for prophylactically administration after implant surgery. Furthermore, results highlight that functionalization of PDMS with Palm and DNase I should not compromise the action of host immune cells. The overall results reinforce the potential of this antimicrobial strategy to fight BAI.